Development of Interactive E-Book of Ferns Materials Through a Scientific Approach With HOTS Problems to Improve Student Learning Outcomes - Sri Rizki Sianturi, Advend; Retnoningsih, Amin; Ridlo, Saiful (Universitas Negeri Semarang, 2021)
This study aims to measure the level of validity, readability, feasibility and effectiveness of interactive e-books. The research method is Research and Development (R&D) according to the syntax of Borg and Gall without a dissemination step. In the needs analysis stage, the results of research to identify ferns that grow in the lowlands, medium plains and highlands of Central Java are used. The results of plant identification were used for e-book development. The result of the initial product readability trial was 86.22%, including very good criteria. The results of the material expert validation for the first stage obtained 77.05% and the second stage results were 84.33%. The result validation of media experts obtained a result of 99.07%. The results of the legibility, validity, and feasibility tests were then tested at a large-scale level. The results of the effectiveness test obtained the pretest average value of 22, 33 and the average posttest score of 88.44. The results of the paired sample t test show a significance of 0.000 <0.05, which means that there is a significant relationship before and after using the interactive e-book. The correlation strength is 0.848, indicating a very high correlation. The average value of the activities of students in the attitude aspect of 3.36 criteria is very good. The average value of activities on the aspects of skills during discussion and practicum is 3.38, very good criteria. It is concluded that the interactive e-book of ferns can be used as a valid, practical, and effective learning resource in SMA / MA and can then be disseminated. The correlation strength is 0.848, indicating a very high correlation. The average value of the activities of students in the attitude aspect of 3.36 criteria is very good. The average value of activities on the aspects of skills during discussion and practicum is 3.38, very good criteria. It is concluded that the interactive e-book of ferns can be used as a valid, practical, and effective learning resource in SMA / MA and can then be disseminated. The correlation strength is 0.848, indicating a very high correlation. The average value of the activities of students in the attitude aspect of 3.36 criteria is very good. The average value of activities on the aspects of skills during discussion and practicum is 3.38, very good criteria. It is concluded that the interactive e-book of ferns can be used as a valid, practical, and effective learning resource in SMA / MA and can then be disseminated.